Studying the modes of electron beam generation in a magnetron gun with a secondary-emission cathode - Dovbnya, A.N.; Zakutin, V.V.; Reshetnyak, N.G.; Dovbnya, N.A. (Вопросы атомной науки и техники, 2006)
Modes of electron beam generation and parameters were investigated using a magnetron injection gun with a secondary-emission cathode depending on the magnetic field value and distribution. For the first time it has been shown that the electron current direction in such source can be varied from axial (along the magnetic field direction) to the radial one (across the magnetic field direction) by controlling the amplitude and magnetic field distribution with retention of secondary emission processes on the cathode. Проведено исследование различных режимов генерации и параметров электронных пучков в магнетронной пушке с холодным металлическим вторично-эмиссионным катодом в зависимости от величины и распределения магнитного поля. Впервые показано, что в таком источнике можно осуществлять изменение направления электронного тока от осевого (вдоль направления магнитного поля) к радиальному (поперек направления магнитного поля), регулируя амплитуду и распределение продольного магнитного поля при сохранении вторично-эмиссионных процессов на катоде. Проведено дослідження різних режимів генерації та параметрів електронних пучків у магнетронній гарматі з холодним металевим вторинно-емісійним катодом в залежності від розподілу магнітного поля. Вперше показано, що в такому джерелі можна отримати зміну напряму електронного струму від осьового (вздовж магнітного поля) до радіального (поперек магнітного поля), змінюючи амплітуду та розподіл магнітного поля при збереженні вторинно-емісійних процесів на катоді.